Analisis Fragmentasi Hasil Peledakan Batugamping dengan Metode Pemrosesan Gambar Digital Menggunakan Perangkat Lunak Wipfrag - Wira Yudha; Aldiyansyah; Laode Jonas Tugo (Universitas Halu Oleo, 2024)
Monitoring and evaluation of blast fragmentation are critical to achieving the most optimal design and outcomes. Several methods are utilized to assess the effectiveness of blasting in the field, one of which is the digital image analysis method, which has gained popularity in recent years. This study aims to apply the digital image analysis technique to rock fragments resulting from blasting and compare the results with empirical analysis using the Kuz-Ram equation. The digital image analysis was conducted using data from three blasting activities in a limestone quarry, with the number of blast holes as follows: 130 in blast-01, 86 in blast-02, and 90 in blast-03. The spacing and burden used in the blast designs were 2.5 m and 2 m, respectively, for all three blasting activities. The results revealed that the largest deviation of 60% occurred at the 10 mm sieve size for blast-02 compared to the Kuz-Ram model. Rock fragments from blast-01 passed 80% at a sieve size of ±280 mm, while for blast-02 and blast-03, 80% of the material passed at sizes >=600 mm. The analysis showed that the percentage passing graph R(X) for all three blasting activities, as determined through the Kuz-Ram method, exhibited relatively close values, albeit with some deviations. After analyzing the three blasting activities with identical designs, the results obtained using the WipFrag software demonstrated satisfactory performance for preliminary field monitoring purposes.